2015
DOI: 10.1093/nar/gkv1080
|View full text |Cite
|
Sign up to set email alerts
|

Slx4 and Rtt107 control checkpoint signalling and DNA resection at double-strand breaks

Abstract: The DNA damage checkpoint pathway is activated in response to DNA lesions and replication stress to preserve genome integrity. However, hyper-activation of this surveillance system is detrimental to the cell, because it might prevent cell cycle re-start after repair, which may also lead to senescence. Here we show that the scaffold proteins Slx4 and Rtt107 limit checkpoint signalling at a persistent double-strand DNA break (DSB) and at uncapped telomeres. We found that Slx4 is recruited within a few kilobases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 73 publications
4
59
0
1
Order By: Relevance
“…Efficient recruitment of Slx4 to DNA lesions requires interactions with both Rtt107 and Dpb11 (Fig. 3c) (Cussiol et al 2015; Dibitetto et al 2016). Recent work demonstrated that recognition of γ H2A and phospho-Ddc1 T602 via BRCT-5/6 of Rtt107 and BRCT-3/4 of Dpb11, respectively, is required for dampening of Rad53 signaling (Cussiol et al 2015).…”
Section: Recruitment Of Slx4 To Dna Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Efficient recruitment of Slx4 to DNA lesions requires interactions with both Rtt107 and Dpb11 (Fig. 3c) (Cussiol et al 2015; Dibitetto et al 2016). Recent work demonstrated that recognition of γ H2A and phospho-Ddc1 T602 via BRCT-5/6 of Rtt107 and BRCT-3/4 of Dpb11, respectively, is required for dampening of Rad53 signaling (Cussiol et al 2015).…”
Section: Recruitment Of Slx4 To Dna Lesionsmentioning
confidence: 99%
“…In addition, resection of double strand breaks also generates ssDNA::dsDNA junctions that should support Slx4 recruitment. Indeed, ChIP approaches were successfully used to detect recruitment of Slx4 to an HO-inducible DSB (Dibitetto et al 2016; Leung et al 2016; Toh et al 2010). Congruent with these findings, functional studies also reveal important roles for Slx4 in the response to DSBs (Dibitetto et al 2016).…”
Section: Recruitment Of Slx4 To Dna Lesionsmentioning
confidence: 99%
“…Esse sistema é gerenciado por metabólitos e proteínas que modulam as transições do ciclo celular e influenciam a estabilidade ou as atividades de outras proteínas (DIBITETTO et al, 2016).…”
Section: Maquinário De Reparo Celularunclassified
“…3). 77,80,81 An underlying mechanism may be that Slx4 and Rad9 compete for binding to BRCT1-2 of Dpb11, though Slx4 can also associate with BRCT3-4 of Dpb11. 77,79 It appears that BRCT1-2 and BRCT3-4 of Dpb11 can engage Slx4 and the 9-1-1 complex.…”
Section: The Rtt107 and Slx4 Association And Its Functions In Conjuncmentioning
confidence: 99%